ANALYSIS OF LEUKOCYTE COUNT IN DIABETIC ULCER PATIENTS WITH TYPE 2 DIABETES MELLITUS - Siti Hasnah; Septiani Septiani; Almatin Puspa Dewi (Jurnal Kesehatan Tambusai, 2021)
Background : Diabetic ulcers are a common complication of Diabetes Mellitus (DM) Type 2. People with DM type 2 have the potential to be 15-25% experiencing diabetic ulcers during their lifetime. An increase in leukocytes may indicate an infection or inflammation. Purpose : This research aims to find out the analysis of the number of leukocytes in diabetic ulcer patients in Diabetes Mellitus type 2. Methods : This type of research is descriptive with cross sectional design. The research was conducted at Bhayangkara TK.I R.Said Sukanto Hospital in May-June 2021. The sample is a diabetic ulcer in DM type 2 that performs a complete blood test with a total of 35 samples. Its independent variables are gender, age, and long suffering from DM type 2. The dependent variable is the number of leukocytes. Data is collected using primary and secondary data. Analyzed univariate and bivariate using SPSS fisher exact test. Result Most respondents had number of leukocytes >10,000/uL which was 27 respondents (77.1%). There is an age correlation with the number of leukocytes, p-value 0.006, OR value of 13.2. There is a sex correlation with the number of leukocytes, p-value 0.032, OR value of 8.57. There is a long-suffering correlation with the number of leukocytes, p-value 0.016, OR value of 12.5. Conclusion :There is a relationship between the number of leukocytes with diabetic ulcer patients with type 2 diabetes mellitus with age, gender and duration of diabetes.